Timing of Resource Availability Drives Divergent Social Systems and Home Range Dynamics in Ecologically Similar Tree Squirrels - Mazzamuto, Maria Vittoria; Merrick, Melissa J.; Bisi, Francesco; Koprowski, John L.; Wauters, Lucas; Martinoli, Adriano (Frontiers in Ecology and Evolution, 2020)
Intraspecific variation in home range size has important implications for the distribution of animals across landscapes and the spatial structuring of population, community and ecosystem processes. Among species of similar trophic guild and body mass, differences in home range size can reflect extrinsic variables that exert divergent selective forces upon spacing behavior and social organization. We tested predictions about how resource availability and timing influence social system, home range size and territoriality in two tree squirrel species of similar size and ecological niches but that differ in foraging strategy and social organization. We estimated home range size and intraspecific home range core overlap in the Mt. Graham red squirrel (Tamiasciurus fremonti grahamensis; Arizona USA; MGRS) and the Eurasian red squirrel (Sciurus vulgaris; Alps, Italy; ERS) as functions of species, sex, season, and individual’s body mass. However, body mass did not explain differences found between the two species. We found MGRS home ranges being 3 times smaller with higher core area exclusivity compared to ERS in all seasons. In fact, territorial MGRS evolved in a system of brief resource pulses and are larder hoarders, whereas ERS experience prolonged resource availability and are non-territorial. Only male MGRSs increased their home range during the breeding season, reflecting interspecific differences in social organization and mating behavior. Male ERS home ranges always overlap with several females to enhance mating success, while male and female MGRS maintain nearly exclusive territories throughout the year. Only during spring and summer males temporarily leave their food-based territory to increase mating opportunities with neighboring estrus females. Home range comparisons between ecologically similar species emphasized the importance of divergent extrinsic factors in shaping variability in body size – home range size scaling relationships. Timing in resource availability influenced the social structure and space use in tree squirrels of similar body size, highlighting how the coevolution of arboreal squirrels with conifer tree species has shaped their natural history.